Nuck Canal Endometriosis Following IVF Attempts in a Young Patient—Report of a Case - Maria Papadoliopoulou; Ioannis Margaris; Athanasios Giannakis; Menelaos G. Samaras; Nikolaos V. Michalopoulos; Panayiotis Kokoropoulos; Ioannis Panayiotides; Nikolaos Arkadopoulos (Clinics and Practice, 2024)
Introduction: Endometriosis is a common benign condition affecting 10–15% of women of reproductive age. An unusual site of endometriosis is the canal of Nuck, which is a physiologically obliterated space in women spanning the area from the deep inguinal ring to the labia majora. Case presentation: A 37-year-old woman, with a past medical history of several in vitro fertilization attempts, presented with a right-sided painful inguinal mass. She was subsequently offered surgical exploration and excision of the lesion, which revealed the presence of endometrial glands and stroma. Discussion: Despite being a relatively common and benign pelvic condition, endometriosis can rarely manifest in the inguinal region, within the canal of Nuck. The treating physician should be cognizant of Nuck canal endometriosis, especially in young female patients presenting with an irreducible mass in the inguinal region and associated cyclic pain or infertility. Conclusion: When clinically and radiologically suspected, surgical excision is indicated to establish the diagnosis, provide symptomatic relief and guide further decision making.